Katekese Digital bagi Anak Muda sebagai Ruang Pertemuan Iman dalam Konteks Media Sosial - Tryepina Paulina Nona; Monica Innanda Chiaralazzo; Intansakti Pius X (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2026)
The development of digital culture has significantly changed the communication, relationships, and spirituality of the younger generation, requiring the Church to reconsider its catechetical methods in the context of social media. This article aims to analyze digital catechesis as a space where faith can develop for the younger generation, by examining the theological foundations, the dynamics of digital culture, and the challenges and models for its development. This study adopts a literature review method by conducting a systematic review of Church Magisterial documents, theological works, and academic research related to the religiosity of the younger generation in the digital environment. The research findings indicate that social media can become a place of faith encounter if catechesis focuses not only on the delivery of religious content but also offers a relational experience that is dialogical, participatory, and community-oriented. However, there are serious challenges such as the risk of superficiality, spiritual consumption, the dominance of algorithms, the commodification of religious content, and the issue of doctrinal authority in the digital space. Therefore, the development of digital catechesis must be based on Christocentrism, fidelity to Church teaching, and a combination of online guidance and concrete sacramental life. With an approach that takes context and reflection into account, digital catechesis has the potential to be a significant and transformative tool of evangelization for young people in the evolving culture of social media.